Ecotheology-Based Multicultural Islamic Education as a Strategy for Strengthening Moderate Character and Environmental Awareness - Haetami, Husnul; Suprapto, Suprapto; Mustain, Mustain (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2026)
The escalating global environmental crisis—characterized by ecological degradation, climate change, and declining environmental awareness—poses serious challenges to educational institutions, including Islamic education. This study examines the integration of ecotheology within multicultural Islamic education as a strategic approach to strengthening moderate religious character and enhancing environmental awareness among learners. The main issue addressed is the limited incorporation of ecological ethics and multicultural values in prevailing instructional practices, which often prioritize cognitive achievement while insufficiently fostering moral responsibility toward social pluralism and environmental stewardship. Employing a qualitative descriptive method through systematic literature review and document analysis, followed by thematic content analysis, this research develops an integrative educational model linking theological foundations, multicultural pedagogy, and praxis-oriented learning. The findings demonstrate that embedding ecotheological principles—particularly stewardship (khilāfah), balance (mīzān), and trust (amānah) within dialogical and inclusive pedagogical strategies contributes substantially to the formation of moderate character traits, including tolerance, empathy, cooperation, and peaceful coexistence, alongside the internalization of pro-environmental attitudes and sustainable behaviors. The study concludes that ecotheology-based multicultural Islamic education constitutes a transformative paradigm for cultivating holistic learners who are spiritually grounded, socially harmonious, and ecologically responsible, thereby supporting the realization of sustainable and peaceful communities